Cyber Threats to the Supply Chain: How Cyber Intelligence Informs Best Practices for Operational Security (Journal of The Colloquium for Information Systems Security Education, 2014)
Cyber threats to the supply chain of commercial Information, Communication and Technology (ICT) products, as well as, espionage activities targeting defense manufacturing facilities necessitates a multidisciplinary approach to be used. The integration of cyber intelligence can assist in building a framework for best practices to mitigate activities of Advanced Persistent Threat (APT) groups at the point of origin. Lower tier suppliers and vendors who provide raw materials and commercial off the shelf (COTS) component parts comprise the exposed soft underbelly most vulnerable to compromise. These lower tiers in the supply chain are the source of greatest disruption and vulnerability due to the opacity of security oversight upstream and are the key to building supply chain resilience.